Meningkatkan Keterampilan Membaca Intensif Menggunakan Model Problem Based Learning, Group Investigation Dan Snowball Throwing Pada Siswa Sekolah Dasar - Fitri Noorzainah; Susilawaty . (CV. ITTC INDONESIA, 2024)
This study contains problems regarding student learning outcomes which are classified as low, precisely in intensive reading learning with predominantly scores below the KKM 70 and in terms of classical ≤80, those with scores ≥60. This can happen because learning seems monotonous, learning does not involve students actively, learning is less meaningful and less active, learning situations tend to be monotonous in one direction, there is a lack of use of media to support learning. A possible solution to suggest is to implement the Problem Based Learning, Group Investigation and Snowball Throwing learning models. Next, this research is aimed at analyzing improvements in the quality of teacher activities and increasing student learning outcomes. The research was carried out over a period of 2 cycles with 3 meetings on the subject of 9 male students and 11 female students in class IV at SDN Sungai Miai 11 Banjarmasin. The research resulted in findings that the activities of teachers and students, along with student learning outcomes, showed improvement and met the success indicators during the three meetings conducted